Facioscapulohumeral muscular dystrophy: a review of pathogenesis, clinical symptoms, and treatment - Mikalauskas, T.; Burnytė, B. (Neurologijos seminarai, 2023)
Facioscapulohumeral muscular dystrophy is the third most common muscular dystrophy characterised by weakness of the face, scapula, upper arm, and other muscles. It can also lead to problems with the eyes, hearing, breathing, heart, and central nervous system. The disease is divided into two types: the first type occurs in 95% of patients and the second type occurs in 5%. The phenotypic differences between the two types are not distinct, both resulting from dysregulation of DUX4 expression leading to skeletal muscle toxicity. The first type is characterised by a reduction in D4Z4 repeats, while the second type is characterised by mutations in genes encoding epigenetic regulators such as SMCHD1. In recent years, significant progress has been made in understanding the pathogenesis, clinical features, and progression of the disease, but there is still no specific treatment due to the obstacles in the development of gene therapy. However, supportive measures, including physiotherapy and orthotics, can help improve muscle function and mobility, slow the progression of the disease, and control other symptoms. The disease can present in many ways, from an asymptomatic form to a life dependent on a wheelchair, so it is important for doctors to keep up to date with the latest information so they can identify this genetic disorder faster and help the patient live a full life.